Integrasi Metode Kano dan Turf dalam Evaluasi Sensori Minuman Cokelat Instan Komersial - Duantra Bergas Ari Kunto; Dase Hunaefi; Budi Nurtama (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2022)
Sensory attribute is one of quality parameter that affects buying intention of consumer for commercial instant chocolate drink product. Evaluation of consumer liking using hedonic method or ideal profile method was not enough to fulfill consumer satisfaction. This research aims to identify sensory attributes which are able to give consumer satisfaction using survey method integrated with structural equation model (SEM), Kano method, and total unduplicated reach and frequency (TURF). Kano method is used to evaluate sensory attributes based on consumer satisfaction, while TURF is used to identify sensory component which is able to increase buying intention of consumers with regard to the range and frequency for chocolate instant commercial drink. Preliminary research conducted by modelling consumer preferences suggested that there was an influence of 0.76 sensory attributes to consumer satisfaction. Seven samples were purchased from market and evaluated by 30 untrained panelists using home use test with an approach of consumer habit to consume hot chocolate drink once a week. The panelists were chosen from people who consume commercial instant chocolate drink. Results of this research showed that sensory attributes creamy (texture) and dark chocolate (color) were attractive features which were able to improve consumer satisfaction. Atribute sweet (taste) was categorized as must-be features, while flavor, aroma, and color were classified as one-dimensional features. Combination of attributes in one category can improve the range to reach the targeted consumers and frequency of consumers towards the product, for example attribute creamy can reach 97%, but combination of attributes creamy and thickness can reach 100% of the targeted consumers.